Perceptions and acceptance of COVID-19 vaccine among pregnant and lactating women in Singapore: a pre-vaccine rollout cross-sectional study - Pooja Agarwal Jayagobi; Chengsi Ong; Kee Thai Yeo; Caleb Chun Wei Lim; Meei Jiun Seet; Lee Koon Kwek; Chee Wai Ku; Jerry Kok Yen Chan; Manisha Mathur; Mei Chien Chua (Singapore Medical Journal)
Introduction: Vaccination is critical in controlling the coronavirus disease 2019 (COVID-19) pandemic. However, vaccine perception and acceptance among pregnant and lactating women is unknown in Singapore. We aimed to determine the acceptance of COVID-19 vaccination among these two groups of women in Singapore and the factors associated with vaccine acceptance. Methods: We conducted an anonymous, online survey on the perceptions of the COVID-19 vaccine and its acceptance by pregnant and lactating women at a tertiary maternal and child hospital in Singapore from 1 March to 31 May 2021. Information on their demographics and knowledge was collected. These factors were assessed for their relationship with vaccine acceptance. Results: A total of 201 pregnant and 207 lactating women participated. Vaccine acceptance rates in pregnant and lactating women were 30.3% and 16.9%, respectively. Pregnant women who were unsure or unwilling to take the vaccine cited concerns about safety of the vaccine during pregnancy (92.9%), while lactating women were concerned about its potential long-term negative effects on the breastfeeding child (75.6%). Factors that were positively associated with vaccine acceptance included a lower monthly household income or education level, appropriate knowledge regarding vaccine mechanism and higher perceived maternal risk of COVID-19. Most pregnant (70.0%) and lactating women (83.7%) were willing to take the vaccine only when more safety data during pregnancy and breastfeeding were available. Conclusion: COVID-19 vaccine acceptance was low among pregnant and lactating women in Singapore. Addressing the safety concerns when more data are available and education on the mechanism of vaccine action will likely improve acceptance among these women.